Outcome measures for oral health based on clinical assessments and claims data: feasibility evaluation in practice - Hummel, Riët (BMC Oral Health, 2017)
BACKGROUND: It is well known that treatment variation exists in oral healthcare, but the consequences for oral health are unknown as the development of outcome measures is still in its infancy. The aim of this study was to identify and develop outcome measures for oral health and explore their performance using health insurance claims records and clinical data from general dental practices. METHODS: The Dutch healthcare insurance company Achmea collaborated with researchers, oral health experts, and general dental practitioners (GDPs) in a proof of practice study to test the feasibility of measures in general dental practices. A literature search identified previously described outcome measures for oral healthcare. Using a structured approach, identified measures were (i) prioritized, adjusted and added to after discussion and then (ii) tested for feasibility of data collection, their face validity and discriminative validity. Data sources were claims records from Achmea, clinical records from dental practices, and prospective, pre-determined clinical assessment data obtained during routine consultations. RESULTS: In total eight measures (four on dental caries, one on tooth wear, two on periodontal health, one on retreatment) were identified, prioritized and tested. The retreatment measure and three measures for dental caries were found promising as data collection was feasible, they had face validity and discriminative validity. Deployment of these measures demonstrated variation in clinical practices of GDPs. Feedback of this data to GDPs led to vivid discussions on best practices and quality of care. The measure ‘tooth wear’ was not considered sufficiently responsive; ‘changes in periodontal health score’ was considered a controversial measure. The available data for the measures ‘percentage of 18-year-olds with no tooth decay’ and ‘improvement in gingival bleeding index at reassessment’ was too limited to provide accurate estimates per dental practice. CONCLUSIONS: The evaluated measures ‘time to first restoration’, ‘distribution of risk categories for dental caries’, ‘filled-and-missing score’ and ‘retreatment after restoration’, were considered valid and relevant measures and a proxy for oral health status. As such, they improve the transparency of oral health services delivery that can be related to oral health outcomes, and with time may serve to improve these oral health outcomes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12903-017-0410-5) contains supplementary material, which is available to authorized users.